2013
DOI: 10.1159/000351939
|View full text |Cite
|
Sign up to set email alerts
|

Skin - ‘That Unfakeable Young Surface'

Abstract: The 20- to 25-year period from the mid-1960s to the early 1990s represents, in many ways, a ‘golden era' in the understanding of skin barrier function, percutaneous penetration and (trans)dermal drug delivery. From the ground-breaking mechanistic work of Scheuplein and Blank, and the ‘gold standard' in vivo skin absorption experiments of Feldmann and Maibach, through the unravelling of the stratum corneum's structural and physicochemical characteristics that make it such an incredible feat of bioengineering, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…SC superstructure can be described with a brick and mortar model, where (im)­permeable bricks represent corneocytes (dead cells), surrounded by a mortar which represents a lipid matrix made of ceramides, fatty acids, and cholesterol . Most compounds have been shown to penetrate by the intercellular pathway, i.e., through the lipid matrix . The presence of ceramides and fatty acids with long saturated chains and cholesterol predispose the SC lipids to occur in the gel phase under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…SC superstructure can be described with a brick and mortar model, where (im)­permeable bricks represent corneocytes (dead cells), surrounded by a mortar which represents a lipid matrix made of ceramides, fatty acids, and cholesterol . Most compounds have been shown to penetrate by the intercellular pathway, i.e., through the lipid matrix . The presence of ceramides and fatty acids with long saturated chains and cholesterol predispose the SC lipids to occur in the gel phase under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Kanda and Watanabe [19 ]demonstrated that estradiol suppresses apoptosis in keratinocytes by promoting Bcl-2 expression and induces the expression of cyclin D2, an important cell-cycle regulatory protein [20]. Estrogen may also play a role in the stratum corneum barrier function [21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…20 Peter Elias' 'brick and mortar' concept of the barrier has been widely accepted and studied in detail using various physical-chemicalstructural and experimental approaches, each contributing to a better understanding of the barrier function. [21][22][23][24][25] As more studies have emerged, it has become clear that the establishment and maintenance of a healthy skin barrier relies on coordinated processes from keratinocyte proliferation to desquamation that must constantly adapt to the environmental conditions (for indepth reviews, please consult "Skin barrier", Elias & Feingold, Eds., 2005). 26 The initially ignored epidermal tight junctions (TJ) and their structural remnants that persist in the SC were shown…”
Section: New Players In the Epidermal Barrier Functionmentioning
confidence: 99%